(untitled) (Research, Society and Development, 2022)
Objective: To verify the effects of face-to-face rehabilitation and telerehabilitation on tolerance to the maximum and submaximal exercise, lung function, fatigue intensity and quality of life of survivors of COVID-19. Methodology: This is a protocol of a longitudinal study, of intervention with a sample for convenience. Adults of both sexes who have been diagnosed with COVID-19 confirmed by RT-PCR will be evaluated. After the assessment, they will receive guidance on how to perform exercises without supervision, will be referred to a face-to-face rehabilitation program or telerehabilitation, according to the results obtained in the six-minute walk test and the presence of comorbidities. Expected Results: Demonstrate the effects of exercise through face-to-face rehabilitation and telerehabilitation after being affected by COVID-19, as well as facilitating the development of treatment protocols aimed at the needs observed, aiming to reduce the repercussions caused by the disease and bring a new look to the physiotherapists who work in clinical practice.